Beyond the Binary: Occupational Gender Stereotypes of Transgender Individuals. - Masters, Stephanie; Peeples, Blake; Barth, Joan M (Sex Roles, 2025)
Using hypothetical hiring scenarios, we compared research participants’ (N = 534) judgements of cis- and transgender applicants’ competence, likelihood of being hired, and co-worker comfort for stereotypical masculine and feminine jobs, as well as jobs high and low in people-orientation. Across masculine and feminine stereotyped occupations, ratings for hiring, competence, and co-worker comfort were more favorable for cisgender applicants compared to transgender applicants with two exceptions: Cis- and trans-men did not significantly differ in ratings for hiring or competence for feminine stereotyped occupations. Transgender applicants were rated especially poorly in people-oriented jobs compared to cisgender applicants. Results suggest an overall bias against transgender applicants, rather than bias grounded in traditional gender stereotypes. The findings highlight the role of broader intolerance for gender nonconformity in workplace bias and emphasize the need for more inclusive hiring practices.